Plagiarism vs copyright / Noraini A. Rahman and Nabilah Abdul Samad - A. Rahman, Noraini; Abdul Samad, Nabilah (Faculty of Information Management, 2015)
Plagiarism can be viewed as a serious illness spread in students' attitude nowadays. This culture is a serious crime in academic world that could involve a disciplinary action to university students. First, we will clarify the meaning. Plagiarism is literally a thief who took the work or ideas of others and claimed it is theirs. This is done without the owner's permission. As the ease of retrieving information from the internet, instead of referring to a book, university students usually blindly take the available information from their search and directly use it. Since this method is more users friendly and enhances the simplicity of 'copy and paste' process from the original document, this way is more preferable while completing their assignment.